ASSA14-12-14 Long-Term Outcomes of Coronary Stenting in Women versus Men: Results from A Registry To Evaluate Safety And Effectiveness Of Everolimus Drug Eluting Stent For Coronary Revascularisation. (1st December 2014) - Han, Y; Xu, K; Liu, H; Ma, Y; Xu, B; Yang, Y
Abstract : Backgroud: Although procedural success rates are similar by sex, it remains unclear whether long-term outcomes exist between the sexes. Methods: Data on 1900 Chinese patients from a registry evaluating safety and effectiveness of everolimus drug eluting stent for coronary revascularisation (SEEDS) were analysed to compare long-term outcomes by sex. Results: Female patients (n = 492) were older (63.27 ± 8.38 vs 58.38 ± 9.55, p < 0.05), had more diabetes (31.1% vs 26.4%, p < 0.05) and hypertentions (71.5% vs 61.7%, p < 0.05) than male patients (n = 1408). At one-year follow-up, there was less target vessel failure in female patients than male patients (4.67% vs 6.39%, p < 0.05). There was a trend that rate of cardiac death (0.41% vs 0.50%, p > 0.05), myocardial infarction (3.25% vs 3.48%, p > 0.05), stent thrombosis (0.41% vs 0.64%, p > 0.05) and bleeding (1.22% vs 1.49%, p > 0.05) was lower in female patients. Conclusions: Women undergoing everolimus drug eluting stent implantation have a slightly higher risk than men, but have better long-term survival, especially for rate of target vessel failure.